Persepsi Siswa Terhadap Penerapan Metode Ceramah Plus Dan Metode Imitasi Pada Pembelajaran Penyajian Karya Musik Di SMA Negeri 3 Pariaman - Patdila Ningsih Fardila; Ardipal Ardipal (FBS Universitas Negeri Padang, 2020)
This study aims to reveal the students ' perception on the application of the lecture method plus and The imitation method applied by the art of culture teacher at SMA Negeri 3 Pariaman on learning presentation of musical works. This research is a type of quantitative study with a descriptive analysis approach. This Data is derived from the results of poll distribution, interviews, and observations, then processed using the TCR score formula and percentages. The first indicator in Questionnaire 1 isAcceptance. It shows how well the students receive the treatment and procedures fromthe teachers who apply the plus lecture method when teaching in the classroom. The score obtained from this indicator is 82, and it is categorized Very well. The second indicator is Understanding. It showshow well the students understand the whole material taught by the the teachers who applied the plus lecture method in the classroom. The score obtained from this indicator is 70.5, and it is categorized Good. The third one is the Assessment indicator. It showsthe students' views towards the assessment given by the teachers who applied the plus lecture method on all aspects of the assessment available to students. The score obtained is 85 3, and it is categorized Very Good. The total score of the three indicators in questionnaire 1 was 238.The first indicator in Questionnaire 2 is Acceptance.It shows how well students receive the learning process given by the teachers applying the imitation method. The score obtained is 97, and it is categorized Very Good. The second indicator isUnderstanding. It shows how well students understand the materials taught and exemplified by the teachers who apply the imitation method to students. The score obtained is 93.3, and it is categorized Very Good. The third one isAssessment indicator. It showsthe students' views towards the accuracy of the teachers assessments viewed from various assessment aspects. The score obtained is 86, and it is also categorized Very Good. The total score of the three indicators is 276.